The clinical diagnosis of Obstructive Sleep Apnea Syndrome (OSAS) - Baiardi, Simone; Cirignotta, Fabio (La Medicina del Lavoro, 2017)
Obstructive Sleep Apnea Syndrome (OSAS) is the most frequent sleep breathing disorder in the general population. To reach a correct diagnosis, the clinical work-up requires the association of comprehensive clinical evaluation (anamnesis, physical examination) and nocturnal polysomnography. Polysomnographic recordings may differ by number of bio-parameters recorded and setting (in laboratory or at home), and allow the identification of other sleep disorders in addition to the diagnosis of OSAS. Excessive daytime sleepiness (EDS) is the most frequent daytime complaint of OSAS patients. Its evaluation is fundamental in subjects with suspected OSAS and concomitant high risk of sleep-related accidents due to work-related factors (e.g. professional drivers). To test EDS, physicians may use subjective (questionnaires) and/or objective (polysomnografic or performance tests) measures. Objective tests are more advisable, but to date they are time consuming and expensive. Objective tests less time–consuming and easily applicable to clinic practice are being evaluated.